Ambrisentan for sarcoidosis associated pulmonary hypertension - Judson, M.A.; Highland, KB.; Kwon, et al., S. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2011)
Background: Sarcoidosis associated pulmonary hypertension (SAPH) is associated with significant morbidity and mortality. There is a paucity of information concerning therapy for this condition. Methods:We performed a prospective, open-label, proof of concept trial of ambrisentan for SAPH. 21 subjects with SAPH received 5 mg/day of ambrisentan for 4 weeks and then 10/mg day for 20 subsequent weeks. Results: No significant change was noted in the 6-minute walk distance over the course of the study (mean change between week 0 and 24: 9.8 ± 54.6 meters, p: NS). There were also no significant differences between weeks 0 and 24 in terms of dyspnea as measured by the modified Borg scale, serum brain naturetic peptide, diffusing capacity, and quality of life as measured by the Short Form-36. There was a high dropout rate: overall: 11/21, 52%; social reasons: 3/21, 14%; medical reasons: 8/21, 38% because of dyspnea: 6/21, 29% and/or edema :4/21, 19%. Of those who completed the 24 week study (10/21, 48%), there was an improvement in theirWHO functional class and a marked improvement in their health related quality of life as measured by the St. George Respiratory questionnaire (-15.3 ± 25.0).However both these improvments did not reach statistical significance possibly because of the small sample size. Conclusion: Although ambrisentan was not well tolerated by many of these subjects with SAPH, in those who remained in this 24-week trial, improvements in WHO functional class and in health related quality of life suggested a possible benefit of this drug in selected patients.